2015
DOI: 10.1007/s10750-015-2283-4
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton colonization patterns. Is species richness depending on distance among freshwaters and on their connectivity?

Abstract: Phytoplankton assemblages in two Sicilian water bodies were compared to test the hypothesis that colonization events and the successful establishment of a new species in an aquatic ecosystem may depend on the number of water bodies in a given area and on their relative distance. The two ecosystems are both natural, shallow lakes and they are protected sites hosting a rich avifauna. Lake Biviere di Gela is located in an area with a high density of ponds, whereas Lake Pergusa is an isolated waterbody without oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 46 publications
0
10
0
1
Order By: Relevance
“…Several recent studies have stressed the importance of hydrological connectivity of ponds on general biodiversity. It has been shown that connectivity between ponds increases the species richness of macrophytes (Akasaka and Takamura, 2012), fish (Uchida and Inoue, 2010), phytoplankton (Naselli-Flores et al., 2016) and amphibians (Ribeiro et al., 2011). Although individual SSWBs have lower average alpha diversity than large water bodies, at a regional scale they typically have high gamma diversity (Williams et al., 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have stressed the importance of hydrological connectivity of ponds on general biodiversity. It has been shown that connectivity between ponds increases the species richness of macrophytes (Akasaka and Takamura, 2012), fish (Uchida and Inoue, 2010), phytoplankton (Naselli-Flores et al., 2016) and amphibians (Ribeiro et al., 2011). Although individual SSWBs have lower average alpha diversity than large water bodies, at a regional scale they typically have high gamma diversity (Williams et al., 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Temporary ponds are generally small (from 10 −2 to 10 7 m 2 ) and often grouped in spatial clusters [495]. Their biotic communities should, therefore, be considered as metacommunities, and spatial factors should be included when analyzing their dynamics (e.g., [496]).…”
Section: Pondsmentioning
confidence: 99%
“…The successful colonization and establishment in a new environment by external microbial communities depend on the order of arrival of the colonizers, also referred to as the 'priority effect'. The priority effect has already been used to explain successful colonization of new habitats by microorganisms in aquatic ecosystems (Symons and Arnott, 2014;Incagnone et al, 2014;Naselli-Flores et al, 2016). Further, in microcosm experiments, Werner and Kiers (2015) showed that the arrival order of arbuscular mycorrhizas influenced the successful colonization and future development of root-associated fungal communities in soil.…”
Section: Origin Of Microbial Pioneers In Deglaciated Soilsmentioning
confidence: 99%